SPACE DIPLOMACY IN UZBEKISTAN’S FOREIGN POLICY: STRATEGIC CHOICE, GEOPOLITICAL TRANSFORMATION, AND PROSPECTS FOR REGIONAL LEADERSHIP (Journal of Multidisciplinary Sciences and Innovations, 2026)
This article analyzes the strategic significance of space diplomacy in the contemporary system of international relations and its growing role in Uzbekistan’s foreign policy. In the twenty-first century, space technologies have become one of the key factors determining states’ economic development, national security, international image, and geopolitical influence. Consequently, space diplomacy is increasingly emerging as a distinct instrument of foreign policy. Uzbekistan has recently intensified its engagement in the space sector through the establishment of the UzSpace Agency in 2019, accession to the United Nations Committee on the Peaceful Uses of Outer Space (COPUOS) in 2022, and the expansion of cooperation with international space companies and organizations. The study employs historical-comparative, empirical, institutional, and analytical methods. The article examines the transformation of the space sector in Central Asia, Uzbekistan’s space strategy, soft power policy, international partnerships, technological challenges, and future prospects. The findings demonstrate that space diplomacy is becoming an important tool for geopolitical influence, technological modernization, and regional leadership for Uzbekistan.